Enhancing Understanding of Acute Ischemic Stroke Research in the Elderly: A Discussion on the Importance of Inflammatory Markers [Letter] - Tang Z; Zeng M; Tang Z (Clinical Interventions in Aging)
Zhongqiu Tang, Mengjun Zeng, Zhaohui Tang Department of Oncology, The Central Hospital of Yongzhou, Yongzhou, Hunan, 425000, People’s Republic of ChinaCorrespondence: Zhaohui Tang, Email tangzhaohui2023@163.com